The Use of Electronic Consent (eConsent) Within the Ketamine for Long-Lasting Pain Relief After Surgery (KALPAS) Multicenter Trial - Doan LV; Burr J; Perez R; Martinez H; Cuevas R; Watt K; Wang J (Journal of Pain Research)
Lisa V Doan,1,2 Jeri Burr,3 Raven Perez,1,2 Hamleini Martinez,1,2 Randy Cuevas,1,2 Kevin Watt,3 Jing Wang1,2,4 1Department of Anesthesiology, Perioperative Care, and Pain Medicine, New York University Grossman School of Medicine, New York, NY, USA; 2Interdisciplinary Pain Research Program, New York University Grossman School of Medicine, New York, NY, USA; 3Department of Pediatrics, University of Utah, Salt Lake City, UT, USA; 4Department of Neuroscience and Physiology, New York University Grossman School of Medicine, New York, NY, USACorrespondence: Lisa V Doan; Jing Wang, Department of Anesthesiology, Perioperative Care, and Pain Medicine, New York University Grossman School of Medicine, New York, NY, USA, Email Lisa.doan@nyulangone.org; jing.wang2@nyulangone.orgBackground: The informed consent process has traditionally taken place in person. The introduction of electronic consent (eConsent) has made remote consenting processes possible. Use of eConsent has increased since the COVID-19 pandemic. It has streamlined the process of consenting patients and has been shown to benefit the research study team and participants.eConsent in the Ketamine Analgesia for Long-Lasting Pain Relief After Surgery (Kalpas) Study: The KALPAS study is a multicenter, double-blind, randomized controlled study investigating the effectiveness of ketamine in reducing chronic post-mastectomy pain in women undergoing mastectomy for oncologic indication. The study uses a two-part consent form consisting of a master consent with information applicable to all sites and site-specific information. All potential participants receive the full two-part consent form for review. When signing the eConsent, however, all potential participants are provided with a concise summary of the informed consent document, an approach not widely used by multicenter studies. eConsent has been noted to be beneficial to research staff when trying to gather informed consent from participants who live far away from the hospital, want to include their family and friends, and for researchers who can approach patients outside of their clinical appointments.Conclusion: The ability to consent patients remotely has allowed for a flexible workflow within sites and a more patient-centric process that focuses on including loved ones in the discussion and scheduling time to speak to a principal investigator. Demand for eConsent will likely continue in the post-COVID era, and use of a concise summary can allow for a more efficient consenting process.Keywords: electronic consent, clinical trials, informed consent, concise summary